PENGARUH PENGGUNAAN FILM DOKUMENTER RENGASDENGKLOK TERHADAP HASIL PEMBELAJARAN SEJARAH KELAS XI DI SMA NEGERI 9 KOTA JAMBI - Fitriana, Firly Sagita; Azmi, Ulul; Yanto, Ferry (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This study aimed to determine the effect of the documentary film "Rengasdengklok" on student learning outcomes in History. The research method used was an experimental research method with a pre-test and post-test control group design. The subjects were 11th-grade students divided into two groups: an experimental group and a control group. The research instrument was a learning outcome test administered before and after the treatment. Based on the data analysis, it was found that the use of the documentary film "Rengasdengklok" had no significant effect on students' History learning outcomes. This indicates that the documentary films significant contribution to improving student learning outcomes. The results of this study are expected to serve as a reference for teachers in selecting appropriate learning media and as a reference for further research related to the effectiveness of using learning media in improving learning outcomes.